Tree of Pearls, Queen of Egypt - Zaydān, Jirjī, 1861-1914 (Book collections on Project MUSE., 2012)
Shajar al-Durr, known as Tree of Pearls, was one of the most famous Arab queens and the only woman in the medieval Arab world to rule in her own name. Her story is one element of a much larger story of the unsettled political climate of thirteenth century Egypt. In this eponymous novel, the author charts the fall of the Ayyubid Dynasty and the rise of the Mamluke Dynasty through the adventures of Tree of Pearls and Rukn al-Din Baybars, a young Mamluke commander who eventually triumphs as the ruler of Egypt. War, political intrigue, murder, and a female ruler who was born a slave combine to give readers an irresistible story, while the book's observations on royal politics and subverted gender roles offer readers a detailed glimpse of the cultural milieu of the time.